The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22063177
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of TRPV1 Ion Channel in the Canine Peripheral Blood Mononuclear Cells

Abstract: TRPV1, known as a capsaicin receptor, is the best-described transient receptor potential (TRP) ion channel. Recently, it was shown to be expressed by non-excitable cells such as lymphocytes. However, the data regarding the functional expression of the TRPV1 channel in the immune cells are often contradictory. In the present study, we performed a phylogenetical analysis of the canine TRP ion channels, we assessed the expression of TRPV1 in the canine peripheral blood mononuclear cells (PBMC) by qPCR and Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
1
0
0
Order By: Relevance
“…Macrophages of the skin of the AD-dogs showed GPR55-IR, a finding consistent with those obtained in the macrophages of rodents, humans ( 101 , 102 ) and dogs ( 43 ). Macrophages of the skin of the AD-dogs also expressed TRPV1-IR; this finding supported a recent study which showed the expression of TRPV1 on both the mRNA and the protein levels in canine peripheral blood mononuclear cells and indicated that this ion channel was functional ( 103 ). In addition, there is a study on mice supporting the role of the TRPV1 channel in macrophage activation and the effectiveness of a subset of TRPV1 channel antagonists in suppressing inflammatory responses ( 104 ).…”
Section: Discussionsupporting
confidence: 88%
“…Macrophages of the skin of the AD-dogs showed GPR55-IR, a finding consistent with those obtained in the macrophages of rodents, humans ( 101 , 102 ) and dogs ( 43 ). Macrophages of the skin of the AD-dogs also expressed TRPV1-IR; this finding supported a recent study which showed the expression of TRPV1 on both the mRNA and the protein levels in canine peripheral blood mononuclear cells and indicated that this ion channel was functional ( 103 ). In addition, there is a study on mice supporting the role of the TRPV1 channel in macrophage activation and the effectiveness of a subset of TRPV1 channel antagonists in suppressing inflammatory responses ( 104 ).…”
Section: Discussionsupporting
confidence: 88%